Fluidization behavior of wood/sand mixtures - Ramakers, Bram J.; de Ridder, Ronny; J.A.M. Kerkhof, Piet (Maderas. Ciencia y Tecnología, 2014)
In conversion of biomass to secondary energy carriers, several routes are possible, such as gasification, combustion and pyrolysis. In many of these processes it is necessary or advantageous to dry the biomass before further processing. For wooden biomass, fluidized bed drying in superheated steam is a promising option. Given the difficulty to fluidize wood particles alone, it is very common to fluidize these kinds of particles with sand. This also gives better defined fluidization behavior. Especially when the wood particles come in various size and shape (i.e. from sawdust to chopped wood), this gives a more reliable scale-up. Also heat transfer to the wood particles may benefit from the use of sand. However, not much is known about fluidization behavior in pressurized steam of binary mixtures with large particle size ratio and large particle density ratio. Therefore minimum fluidization velocity and bed porosity of wood/sand mixtures in air have been experimentally determined and compared to correlations known from literature. The experimental values show a clear trend, but correlations from literature appear not to be very accurate. So more experiments have to be done to find a correlation that gives more accurate predictions in case of the specific particles used in this work. From segregation experiments could be found that, to keep the wood/sand bed well-mixed, finer sand (0.1-0.5 mm) with maximum 10 weight-% wood should be used, and the superficial gas velocity should be at least 3-4 times the minimum fluidization velocity.